2016
DOI: 10.1007/s10334-015-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the effects of magnetization transfer asymmetry on inhomogeneous magnetization transfer (ihMT) at ultra-high magnetic field (11.75 T)

Abstract: MTRasym is not a confounding factor for ihMT quantification, even at ultra-high field, as long as MTRasym is restricted to ±4 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…At ultra‐high magnetic field strength, efficient correction of MT asymmetry signal contributions also requires the frequency offsets Δ f to be applied relative to a frequency center f c , slightly shifted to f c = −100 Hz from the free water resonance frequency . The ihMT ratio is defined by ihMTR = ihMT/ S 0 , where S 0 is the signal measured with the RF saturation power set to zero.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At ultra‐high magnetic field strength, efficient correction of MT asymmetry signal contributions also requires the frequency offsets Δ f to be applied relative to a frequency center f c , slightly shifted to f c = −100 Hz from the free water resonance frequency . The ihMT ratio is defined by ihMTR = ihMT/ S 0 , where S 0 is the signal measured with the RF saturation power set to zero.…”
Section: Methodsmentioning
confidence: 99%
“…This property has not been fully appreciated in our previous human studies, because these were focused on areas of interest located in the brain and relatively low power intensities were used, as imposed by regulatory energy deposition limitations. Conversely, preliminary studies performed on mice using high power levels have evidenced a non‐negligible ihMT signal in muscle (Mu), and in vitro studies have also revealed a non‐zero ihMT signal in short T 1D components, such as wood or hair . In this context, it is appropriate to envision ihMT as a T 1D ‐weighted imaging modality, for which various contrast regimes and tissue sensitivity could apply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ihMT implementations have mostly consisted of long trains of soft RF saturation pulses followed by fast readout modules (1)(2)(3)(16)(17)(18)(19). In the following study, we refer to these kinds of implementation as ihMT-prep sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such indexes include MT ratio (MTR) (Dousset et al, 1992), MT saturation (MTsat) (Helms et al, 2008), and MTR difference observed in the recently proposed inhomogeneous MT experimental method (ihMTR) (Varma et al, 2015a). Some of these quantities, such as MTsat (Boretius et al, 2010) and ihMTR (Prevost et al, 2016) showed a promise in ultra-high field anatomical neuroimaging due to their capability to generate strong contrast between WM and GM on corresponding parametric maps. However, the above indexes are problematic to use for the objective quantitative characterization of pathological changes in tissues due to their complex dependence on the parameters of an imaging sequence and underlying biophysical model describing the MT effect.…”
Section: Introductionmentioning
confidence: 99%